Promoting Inclusive Economic Growth to Combat Inequality and Poverty in Indonesia - Arif Darmawan (Proceedings of AICS - Social Sciences, 2017)
The paradigm of development process in developing countries, especially Indonesia since the 80s, is based on economic development with the output in the form of economic growth. This model focuses on improving the productivity and consumption of households and governments. In fact, economic growth does not guarantee that everyone will benefit equally, which is shown by the disparity of income/inequality in society. Moreover, inequality can have implications for political, economic, social and security, which hinder the implementation of inclusive and sustainable development. Despite the high overall economic growth rates in Indonesia in the past decade, many policy makers and in international organizations have become increasingly concerned that this growth has been too uneven and often accompanied by rising income of inequality and poverty. Consequently, Indonesian government committed its Medium Term Development Plan (RPJM 2015-2019), to promoting inclusive economic growth as one of the directions in economic policy. Inclusive economic growth has become a strategic pillar for guiding the activities of the Asian countries, for instance: Indonesia in its operational strategy. However, there exists no clear definition or indicator to monitor the progress of inclusive economic growth at the country, project, or program level. This paper tries to review existing definitions of inclusive economic growth and proposes strategically view about inclusive economic growth to tackle down inequality and poverty in Indonesia. This paper also suggests that this might be a way forward to implement inclusive economic growth in Indonesia.